Left-ventricular unloading in extracorporeal cardiopulmonary resuscitation due to acute myocardial infarction – A multicenter study. (May 2023) - Thevathasan, Tharusan; Kenny, Megan A.; Krause, Finn J.; Paul, Julia; Wurster, Thomas; Boie, Sebastian D.; Friebel, Julian; Knie, Wulf; Girke, Georg; Haghikia, Arash; Reinthaler, Markus; Rauch-Kröhnert, Ursula; et al.
Abstract: Background: Guidelines advocate the use of extracorporeal cardio-pulmonary resuscitation with veno-arterial extracorporeal membrane oxygenation (VA-ECMO) in selected patients with cardiac arrest. Effects of concomitant left-ventricular (LV) unloading with Impella® (ECMELLA) remain unclear. This is the first study to investigate whether treatment with ECMELLA was associated with improved outcomes in patients with refractory cardiac arrest caused by acute myocardial infarction (AMI). Methods: This study was approved by the local ethical committee. Patients treated with ECMELLA at three centers between 2016 and 2021 were propensity score (PS)-matched to patients receiving VA-ECMO based on age, electrocardiogram rhythm, cardiac arrest location and Survival After Veno-Arterial ECMO (SAVE) score. Cox proportional-hazard and Poisson regression models were used to analyse 30-day mortality rate (primary outcome), hospital and intensive care unit (ICU) length of stay (LOS) (secondary outcomes). Sensitivity analyses on patient demographics and cardiac arrest parameters were performed. Results: 95 adult patients were included in this study, out of whom 34 pairs of patients were PS-matched. ECMELLA treatment was associated with decreased 30-day mortality risk (Hazard Ratio [HR] 0.53 [95% Confidence Interval (CI) 0.31–0.91], P = 0.021), prolonged hospital (Incidence Rate Ratio (IRR) 1.71 [95% CI 1.50–1.95], P < 0.001) and ICU LOS (IRR 1.81 [95% CI 1.57–2.08], P < 0.001). LV ejection fraction significantly improved until ICU discharge in the ECMELLA group. Especially patients with prolonged low-flow time and high initial lactate benefited from additional LV unloading. Conclusions: LV unloading with Impella® concomitant to VA-ECMO therapy in patients with therapy-refractory cardiac arrest due to AMI was associated with improved patient outcomes.